Australian recommendations for EGFR T790M testing in advanced non–small cell lung cancer. Issue 4 (12th July 2017) - John, Thomas; Bowden, Jeffrey J; Clarke, Stephen; Fox, Stephen B; Garrett, Kerryn; Horwood, Keith; Karapetis, Christos S
Abstract: First‐generation epidermal growth factor receptor ( EGFR ) tyrosine kinase inhibitors (TKIs) are used as first‐line therapy in patients with non–small cell lung cancer (NSCLC) harboring a sensitizing mutation in the EGFR gene. Unfortunately, resistance to these therapies often occurs within 10 months of commencing treatment and is mostly commonly due to the development of the EGFR T790M mutation. Treatment with the third‐generation EGFR TKI, osimertinib can prolong progression free survival in patients with the T790M mutation, so it is important to determine the resistance mechanism in order to plan ongoing therapeutic strategies. Here we review the evidence and make recommendations for the timing of T790M mutation testing, the most appropriate specimens to test and the available testing methods in patients progressing during treatment with first line EGFR TKIs for NSCLC.